Damage detection of base-isolated buildings using multi-input multi-output subspace identification. - Yoshimoto, Reiki
A damage detection algorithm of structural health monitoring systems for base-isolated buildings is proposed. The algorithm consists of the multiple input multiple output subspace identification method and the complex modal analysis. The algorithm is applicable to linear and non-linear systems. The story stiffness and damping as damage indices of a shear structure are identified by the algorithm. The algorithm is further tuned for base isolated buildings considering their unique dynamic characteristics by simplifying the systems to single degree of freedom systems. The isolation layer and the superstructure of a base-isolated building are treated as separate substructures as they are distinctly different in their dynamic properties. The effectiveness of the algorithm is evaluated through the numerical analysis and experiment. Finally, the algorithm is applied to the existing 7 story base isolated building that is equipped with an Internet based monitoring system.
Keywords: System identification; Subspace identification; MIMO; Health monitoring; Base-isolation.